Pengaruh Store Atmosphere terhadap Repurchase Intention dengan Service Quality sebagai Variabel Moderasi - Rosita Nurul Azmi; Hendrati Dwi Mulyaningsih; Septiana Ayu Estri Mahani (Bandung Conference Series: Business and Management, 2024)
Abstract. Asep Strawberries is a place/restaurant that is quite popular in the Nagreg area of Bandung, which serves typical Sundanese processed foods such as serving Nasi Liwet Andala. The purpose of this research is to determine the effect of store atmosphere on repurchase intention which is moderated by service quality.The method used is quantitative using nonprobability sampling techniques and purposive sampling techniques. There are two hypotheses in the research which were tested using a simple linear regression approach and MRA (Moderated Regression Analysis) with a total of 130 respondents. The results of the research show that the influence of the store atmosphere on repurchase intention has a positive and significant effect. The results of the moderation test show that service quality strengthens the influence of store atmosphere on repurchase intention at Asep Stroberi Nagreg Bandung. Based on the level of positive and significant relationship of the Service Quality variable as a moderating variable in Store Athmosphere towards Repurchase Intention. Asep Straberi Nagreg Bandung is advised to continue to maintain Service Quality and improve service from employees. So apart from the attractiveness of the Athmospehe Store, the Service Quality factor can also increase interest in repurchasing. Abstrak. Asep stroberi merupakan salah satu tempat / rumah makan yang cukup populer di daerah nagreg bandung, yang menyajikan makanan olahan khas sunda seperti menyajikan nasi liwet andalanya. Tujuan dari penelitian ini untuk mengetahui pengaruh store athmosphere terhadap repurchase intention yang di moderasi oleh service quality.Metode yang di gunakan adalah kuantitatif dengan menggunakan Teknik sampling Nonprobability sampling dan teknik purposive sampling. terdapat dua hipotesis dalam penelitian yang diuji menggunakan pendekatan regresi linier sederhana dan MRA (Moderated Regression Analysis) dengan jumlah responden sebanyak 130.Hasil dari penelitian diketahui bahwa pengaruh store athmosphere terhadap repurchase intention berpengaruh positif dan signifikan. Hasil pengujian moderasi menunjukan service quality memperkuat pengaruh antara store atmosphere terhadap repurchase intention pada Asep Stroberi Nagreg Bandung.Berdasarkan tingkat hubungan positif dan signifikan dari variabel Service Quality sebagai variabel moderasi pada Store Athmosphere terhadap Repurchase Intention. Pihak Asep Stroberi Nagreg Bandung disarankan untuk terus menjaga Service Quality dan meningkatkan pelayanan dari para karyawan. Sehingga selain daya tarik dari Store Athmospehe, faktor Service Quality juga dapat menimbulkan minat beli ulang.